Famílias beneficiárias do Programa Bolsa Família do Munícipio de Várzea Paulista-SP: (des)caminhos na garantia da proteção social e na busca da superação da extrema pobreza - Azevedo, Sidney Rezende (2018)
The purpose of the presente study is to investigate the situations of social helplessness experienced by families that receive any help from the “BolsaFamília” program in the Municipality of VárzeaPaulista -SP. The research is essentially qualitative, where were analyzed aspects related to the objective and subjective conditions of the beneficiary families and the ability to access and evaluate municipal public services, for instance health, education and social assistance. The Evaluations were made through a questionnaire applied at the households address, where it was heard reports of different situations of social abandonment experienced by these families during their lives. Material and symbolic relations between families, and the construction of feminine gender that the PBF has in addition to the discursive elements showed the occurrence of familism and pointed out the feminization of poverty. It was also evaluate how people deal with absence or presence of the State. In which dimension is happening the “non-accountability” of the state and the accountability of the families. The familismphenomenonand the interface with the PBF. The biggest Brazilian program of income transfer faces an articulation difficulty with other social policies, which makes it difficult to overlap the stigma of a social program of poverty relief. We approached different situations of social destitution that accumulates in the family dynamics which demands the offer of social protection .Questions about death in the family, accidents, evictions, famine, constant residential changes, diseases, births, discrimination, landslides, flood, maternity domestic violence, unemployment, and street situation. Situations of disrespect, humiliation and embarrassment that cause ethical-political suffering. The research shows how families, especially women, working class that doesnt have the support of the State and how much the “extended family”, like religious institution and friends/ neighbors can offer and help. In most families, occasional and restricted support. The poor women who live from the work are the same who suffer prejudice and discrimination from the several discriminating agents mentioned in the research. They are exploited by working capital and they occupy the most precarious jobs, even exploited, they need to resist to the perverse logic of social abandonment,low access and quality of the public services that accumulate according to the territory